NATURE AND COLOR; WITH REFERENCE TO ENVIRONMENT: प्रकृति एवं रंग ;पर्यावरण के संदर्भ मेंद्ध - Chauhan, Sadhna (International Journal of Research -GRANTHAALAYAH, 2014)
The relation of human life and nature has been unbroken with the creation of the earth, human has consumed everything obtained from nature for his livelihood and entertainment, on the one hand he receives food, shelter and clothes from nature and on the other hand nature Seeing the scenes and portraying them by the artists is an incredible feeling of peace. Nature, river, trees, plants, mountains and animal birds are all depicted in the paintings painted by the artists first and the color, Tulika, the material that is helpful in drawing them, is also derived from nature. The artists first used colors from nature in their artwork. In tribal folk art, natural colors have been used in Mandana, Phad, Alpana, Madhubani etc. These colors are sometimes made with stones, flowers and leaves. The nature of the forms that we are attracted to and which gives us joy, is not just a replica of the art, but the art forms have been created by being influenced and transformed by the basis of those forms. We rejoice which has no meaning. Only his visceral figure leaves his mark. But the desire for analogy and meaning in some form remains in the picture. The waterfalls, the river, the sea attracts the frequency of the lines in the thick stem of the stem. ' मानव जीवन और प्रकृति का संबध पृथ्वी की रचना के साथ अटूट रहा है, मानव ने प्रकृति से प्राप्त सभी चीजों का उपभोग अपने जीवनयापन और मनोरंजन के लिये किया है, एक ओर उसे प्रकृति से भोजन, आवास और वस्त्र प्राप्त होता है तो दूसरी ओर प्रकृति के दृश्यों को देखकर और कलाकारों के द्वारा चित्रित कर शान्ति की अदभूत अनुभूति होती है। सर्वप्रथम कलाकारों द्वारा जो चित्र चित्रित किये गये उनमें प्रकृति चित्रण नदी, पेड़, पौधे, पर्वत और पशु पक्षी सभी चित्रित किये गये तथा इन्हें चित्रित करने में सहायक सामग्री रंग, तुलिका वह भी प्रकृति से प्राप्त होती है। सर्वप्रथम कलाकारों ने प्रकृति से प्राप्त रंगों का उपयोग अपनी कलाकृति में किया। आदिवासी लोक कला में माण्डना, फड़, अल्पना, मधुबनी आदि में प्राकृतिक रंगों का उपयोग किया गया है। ये रंग कभी कभी पत्थरों , फूलों तथा पत्त्यिों से बनाए जाते है। प्रकृतिमें जिन रूपों की ओर हम आकर्षित होते है तथा जो हमें आनन्द प्रदान करते है, उनकी प्रतिकृति मात्र कला नहीं है उन रूपों का आधार लेकर उनसे प्रभावित होकर तथा उनका रूपांतरण करके कलाकृतियों का निर्माण होता रहा है।‘प्रकृति में अनेक ऐसी आकृतियांे को देखकर हम आनन्दित होते है जिनका कोई अर्थ नहीं होता है। केवल उनकी चाक्षुष आकृति अपनी छाप छोड़ती है। किन्तु चित्र में किसी रूप में सादृश्य की तथा अर्थ की इच्छा बनी रहती है। झरने, नदी, समुद्र में मोटे तने के काठ में रेखाओं की आवृत्ति आकर्षित करती है।‘